2014
DOI: 10.5414/cn108153
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of community-acquired versus hospital-acquired acute kidney injury: a retrospective analysis

Abstract: CA-AKI was found to be considerably more common than HA-AKI and had similar long-term consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 0 publications
0
43
0
Order By: Relevance
“…Even as a relatively new study concept, several risk factors for CA-AKI have been identified, many of which are reflective of those for HA-AKI, such as age, diabetes, congestive HF, CKD, human immunodeficiency virus, obstructive uropathy, and volume depletion [1, 9]. Patients with CA-AKI are more likely to have comorbidities than patients with HA-AKI [17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Even as a relatively new study concept, several risk factors for CA-AKI have been identified, many of which are reflective of those for HA-AKI, such as age, diabetes, congestive HF, CKD, human immunodeficiency virus, obstructive uropathy, and volume depletion [1, 9]. Patients with CA-AKI are more likely to have comorbidities than patients with HA-AKI [17].…”
Section: Discussionmentioning
confidence: 99%
“…Identification in the hospital is more common and typically more severe than CA-AKI as identified in primary care; however, both have been associated with increased mortality [9]. A Veterans Affairs Center study revealed that 23.6% of patients hospitalized from 2004 to 2005 in Upstate New York had AKI, and approximately 78% of those instances were attributed to CA-AKI, indicating that primary care clinics should regularly screen for AKI before the patient deteriorates and requires hospitalization [9]. Additionally, CA-AKI has been shown to be predictive of a poor clinical course, progression to CKD, and death, with 5-year mortality as high as 64% [4, 23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 The present study evaluated the renal effects of optimizing potentially nephrotoxic medications in an older population. The hypothesis is that avoidance of polypharmacy is associated with improved renal function.…”
Section: Introductionmentioning
confidence: 99%